1997
DOI: 10.1111/j.1432-1033.1997.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Solution Structure of Human Angiogenin Determined by 1H,15N‐NMR Spectroscopy — Characterisation of Histidine Protonation States and Pka Values

Abstract: Human angiogenin is a member of the pancreatic ribonuclease superfamily that induces blood vessel foimation. Its three-dimensional solution structure has been determined to high resolution by heteronuclear NMR spectroscopy. 30 structures were calculated, based on a total of 1441 assigned NOE correlations, 64 coupling constants and 50 hydrogen bonds. The backbone atomic rms difference from the mean coordinates is 0.067 ? 0.012 nm and 0.13 nm from the previously determined crystal structure. The sidechain of Gln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 60 publications
7
43
0
Order By: Relevance
“…Although RNase 3 is dimeric in the crystal, the protein fold determined by the two techniques is similar. In addition, NMR studies revealed two conformations for His114 of RNase 5 in solution [240]. The structures of RNase 2 and RNase 7 are given in Figure 4 (panels E and F).…”
Section: Three-dimensional Structures Of Human Antimicrobial Peptidesmentioning
confidence: 99%
“…Although RNase 3 is dimeric in the crystal, the protein fold determined by the two techniques is similar. In addition, NMR studies revealed two conformations for His114 of RNase 5 in solution [240]. The structures of RNase 2 and RNase 7 are given in Figure 4 (panels E and F).…”
Section: Three-dimensional Structures Of Human Antimicrobial Peptidesmentioning
confidence: 99%
“…NMR analysis revealed that human ANG is a relatively well-folded protein, with increased dynamics in some regions (e.g., backbone atoms of ~five residues at both N- and C-termini, and regions 59–70 and 82–95 were shown to possess relatively high root-mean square deviations from their position in the mean structure) [139]. Figure 3D shows that these regions are predicted to be intrinsically disordered.…”
Section: Illustrative Examples Of Idps In Neurodegenerationmentioning
confidence: 99%
“… Schematic diagram of the subsites of the hAng active site. The residues shown were observed in various crystal and NMR structures to be within the sites …”
Section: Introductionmentioning
confidence: 96%